SYNTHESIS AND CHARACTERIZATION OF NAX ZEOLITE MEMBRANE VIA VACUUM SEEDING HYDROTHERMAL METHODTO MINIMIZE DEFECTS - MOHD NAZIR, LIYANA SALWA (2020)
The development of zeolite membranes has been a subject of interest for various application due to its uniform pores characteristic, excellent thermal and chemical stability as well as catalytic and ion-exchange properties. However, the synthesis of zeolite membranes with minimum defects isstill a challenge as there are multiple variables in the synthesis process which need to be controlled. In this work, NaX zeolite crystals and membranes were synthesized via hydrothermal growth method. Synthesis of NaX zeolite crystals were perform with varied synthesis parameters including aging duration and Na2O/Al2O3ratioof synthesis solution.